2020
DOI: 10.1093/qje/qjaa020
|View full text |Cite
|
Sign up to set email alerts
|

Misallocation in the Market for Inputs: Enforcement and the Organization of Production*

Abstract: The strength of contract enforcement determines how firms source inputs and organize production. Using microdata on Indian manufacturing plants, we show that production and sourcing decisions appear systematically distorted in states with weaker enforcement. Specifically, we document that in industries that tend to rely more heavily on relationship-specific intermediate inputs, plants in states with more congested courts shift their expenditures away from intermediate inputs and have a greater vertical span of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(49 citation statements)
references
References 68 publications
3
46
0
Order By: Relevance
“…The same firms are also more likely to acquire firms from the same industry as the affected supplier (Column II). This result is consistent with Boehm and Oberfield (2020), who show that supply chains located in areas with more congested courts are vertically more integrated in India. Overall, the results are consistent with difficulties in establishing new relationships due to court-induced contracting frictions and potential future hold-up problems.…”
Section: Vertical Integrationsupporting
confidence: 91%
See 2 more Smart Citations
“…The same firms are also more likely to acquire firms from the same industry as the affected supplier (Column II). This result is consistent with Boehm and Oberfield (2020), who show that supply chains located in areas with more congested courts are vertically more integrated in India. Overall, the results are consistent with difficulties in establishing new relationships due to court-induced contracting frictions and potential future hold-up problems.…”
Section: Vertical Integrationsupporting
confidence: 91%
“…Courts are essential for firm-to-firm relationships, since they have the ultimate authority to enforce a contract between contracting parties. While courts are an important determinant in choosing business partners (Johnson et al, 2002;Boehm and Oberfield, 2020), the overall effect of court quality on the transmission of shocks is ambiguous. Imagine a downstream firm facing disruptions due to a sudden loss of a supplier that provides inputs and trade credit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boehm (2018) calculates, under a set of conservative assumptions, that on average countries would grow by 18% if enforcement costs were zero. Boehm and Oberfeld (2018) find that a feasible reduction in court congestion alone in India would increase productivity by 5%. In a small survey of Romanian firms, Murrell and Paun (2010) asked about the willingness-to-pay for first-best institutions and found that the transaction costs of exchange are as high as 23% of value added.…”
Section: Introductionmentioning
confidence: 98%
“…All of these papers focus on estimating the coefficients of the interaction terms between a sector's institutional dependence and the jurisdiction's 5 Levchenko (2007) develops a formal macroeconomic model of this phenomenon based on the approach pioneered by Caballero and Hammour (1998). Boehm and Oberfield (2018) present a related microeconomic model. 6 A detailed discussion of some of the advantages of sub-national data can be found in Snyder (2001).…”
Section: Introductionmentioning
confidence: 99%